Power Series Expansion for Tangent Function

From ProofWiki
Jump to navigation Jump to search

Theorem

The tangent function has a Taylor series expansion:

\(\displaystyle \tan x\) \(=\) \(\displaystyle \sum_{n \mathop = 1}^\infty \frac {\left({-1}\right)^{n - 1} 2^{2 n} \left({2^{2 n} - 1}\right) B_{2 n} \, x^{2 n - 1} } {\left({2 n}\right)!}\)
\(\displaystyle \) \(=\) \(\displaystyle x + \frac {x^3} 3 + \frac {2 x^5} {15} + \frac {17 x^7} {315} + \cdots\)


where $B_{2 n}$ denotes the Bernoulli numbers.

This converges for $\left|{x}\right| < \dfrac \pi 2$.


Proof 1

From Power Series Expansion for Cotangent Function:

$(1): \quad \cot x = \displaystyle \sum_{n \mathop = 0}^\infty \frac {\left({- 1}\right)^n 2^{2 n} B_{2 n} \, x^{2 n - 1} } {\left({2 n}\right)!}$


Then:

\(\displaystyle \tan x\) \(=\) \(\displaystyle \cot x - 2 \cot 2 x\) Cotangent Minus Tangent
\(\displaystyle \) \(=\) \(\displaystyle \sum_{n \mathop = 0}^\infty \frac {\left({- 1}\right)^n 2^{2 n} B_{2 n} \, x^{2 n - 1} } {\left({2 n}\right)!} - 2 \sum_{n \mathop = 0}^\infty \frac {\left({-1}\right)^n 2^{2 n} B_{2 n} \, \left({2 x}\right)^{2 n - 1} } {\left({2 n}\right)!}\) by $(1)$
\(\displaystyle \) \(=\) \(\displaystyle \sum_{n \mathop = 0}^\infty \frac {\left({- 1}\right)^n 2^{2 n} \left({1 - 2^{2 n} }\right) B_{2 n} \, x^{2 n - 1} } {\left({2 n}\right)!}\)
\(\displaystyle \) \(=\) \(\displaystyle \sum_{n \mathop = 1}^\infty \frac {\left({- 1}\right)^{n - 1} 2^{2 n} \left({2^{2 n} - 1}\right) B_{2 n} \, x^{2 n - 1} } {\left({2 n}\right)!}\)

$\Box$


Proof 2

We have:

\(\displaystyle \frac x {e^x - 1}\) \(=\) \(\displaystyle \frac x 2 \left({\frac 2 {e^x - 1} }\right)\)
\(\displaystyle \) \(=\) \(\displaystyle \frac x 2 \left({\frac {e^x - e^x + 2} {e^x - 1} }\right)\)
\(\displaystyle \) \(=\) \(\displaystyle \frac x 2 \left({\frac {\left({e^x + 1}\right) - \left({e^x - 1}\right)} {e^x - 1} }\right)\)
\(\displaystyle \) \(=\) \(\displaystyle \frac x 2 \left({\frac {e^x + 1} {e^x - 1} - 1}\right)\)
\(\displaystyle \) \(=\) \(\displaystyle -\frac x 2 + \frac x 2 \left({\frac {e^x + 1} {e^x - 1} }\right)\)
\(\displaystyle \) \(=\) \(\displaystyle -\frac x 2 + \frac x 2 \left({\frac {e^{x/2} + e^{-x/2} } {e^{x/2} - e^{-x/2} } }\right)\) multiplying top and bottom by $e^{-x/2}$


Thus:

\((1):\quad\) \(\displaystyle \frac x 2 \left({\frac {e^{x/2} + e^{-x/2} } {e^{x/2} - e^{-x/2} } }\right)\) \(=\) \(\displaystyle \sum_{n \mathop = 0}^\infty \frac {B_{2 n} } {\left({2 n!}\right)} x^{2 n}\) Definition of Bernoulli numbers


Replacing $x$ with $2 i x$ in the left hand side $(1)$:

\(\displaystyle \) \(\) \(\displaystyle \frac {2 i x} 2 \left({\frac {e^{2 i x / 2} + e^{-2 i x / 2} } {e^{2 i x / 2} - e^{-2 i x / 2} } }\right)\)
\(\displaystyle \) \(=\) \(\displaystyle i x \left({\frac {e^{i x} + e^{-i x} } {e^{i x} - e^{-i x} } }\right)\)
\(\displaystyle \) \(=\) \(\displaystyle x \cot x\) Cotangent Exponential Formulation


Replacing $x$ with $2 i x$ in the right hand side $(1)$:

\(\displaystyle \) \(\) \(\displaystyle \sum_{n \mathop = 0}^\infty \frac {B_{2 n} } {\left({2 n!}\right)} \left({2 i x}\right)^{2 n}\)
\(\displaystyle \) \(=\) \(\displaystyle \sum_{n \mathop = 0}^\infty \left({-1}\right)^n \frac {2^{2 n} B_{2 n} } {\left({2 n!}\right)} x^{2 n}\)
\(\displaystyle \leadsto \ \ \) \(\displaystyle x \cot x\) \(=\) \(\displaystyle \sum_{n \mathop = 0}^\infty \left({-1}\right)^n \frac {2^{2 n} B_{2 n} } {\left({2 n!}\right)} x^{2 n}\)
\(\displaystyle \leadsto \ \ \) \(\displaystyle \cot x\) \(=\) \(\displaystyle \sum_{n \mathop = 0}^\infty \left({-1}\right)^n \frac {2^{2 n} B_{2 n} } {\left({2 n!}\right)} x^{2 n - 1}\)


Then from Cotangent Minus Tangent:

$\tan x = \cot x - 2 \cot 2 x$

from which:

\(\displaystyle \tan x\) \(=\) \(\displaystyle \sum_{n \mathop = 0}^\infty \frac {\left({- 1}\right)^n 2^{2 n} B_{2 n} } {\left({2 n}\right)!} x^{2 n - 1} - 2 \sum_{n \mathop = 0}^\infty \frac {\left({-1}\right)^n 2^{2 n} B_{2 n} } {\left({2 n}\right)!} \left({2 x}\right)^{2 n - 1}\) by $(1)$
\(\displaystyle \) \(=\) \(\displaystyle \sum_{n \mathop = 0}^\infty \frac {\left({- 1}\right)^n 2^{2 n} (1 - 2^{2 n}) B_{2 n} } {\left({2 n}\right)!} x^{2 n - 1}\)
\(\displaystyle \) \(=\) \(\displaystyle \sum_{n \mathop = 1}^\infty \frac {\left({- 1}\right)^{n - 1} 2^{2 n} (2^{2 n} - 1) B_{2 n} } {\left({2 n}\right)!} x^{2 n - 1}\)

$\Box$


Proof of Convergence

By Combination Theorem for Limits of Functions we can deduce the following.

\(\displaystyle \) \(\) \(\displaystyle \lim_{n \mathop \to \infty} \left \lvert {\frac {\frac {\left({-1}\right)^n 2^{2 n + 2} \left({2^{2 n + 2} - 1}\right) B_{2 n + 2} } {\left({2 n + 2}\right)!} x^{2 n + 1} } {\frac {\left({-1}\right)^{n - 1} 2^{2 n} \left({2^{2 n} - 1}\right) B_{2 n} } {\left({2 n}\right)!} x^{2n - 1} } } \right \rvert\)
\(\displaystyle \) \(=\) \(\displaystyle \lim_{n \mathop \to \infty} \left \lvert {\frac {\left({2^{2 n + 2} - 1}\right)} {\left({2^{2 n} - 1}\right)} \frac 1 {\left({2 n + 1}\right) \left({2 n + 2}\right)} \frac {B_{2 n + 2} } {B_{2 n} } } \right \rvert 4 x^2\)
\(\displaystyle \) \(=\) \(\displaystyle \lim_{n \mathop \to \infty} \left \lvert {\frac {2^{2 n + 2} - 1} {2^{2 n} - 1} } \right \rvert \left \lvert {\frac 1 {\left({2 n + 1}\right) \left({n + 1}\right)} \frac {B_{2 n + 2} } {B_{2 n} } } \right \rvert 2 x^2\)
\(\displaystyle \) \(=\) \(\displaystyle \lim_{n \mathop \to \infty} \left \lvert {4 \frac {2^{2 n} } {2^{2 n} - 1} - \frac 1 {2^{2 n} - 1} } \right \rvert \left \lvert {\frac 1 {\left({2 n + 1}\right) \left({n + 1}\right)} \frac {B_{2 n + 2} } {B_{2 n} } } \right \rvert 2 x^2\)
\(\displaystyle \) \(=\) \(\displaystyle \lim_{n \mathop \to \infty} \left \lvert {4 + \frac 4 {2^{2 n} - 1} - \frac 1 {2^{2 n} - 1} } \right \rvert \left \lvert {\frac 1 {\left({2 n + 1}\right) \left({n + 1}\right)} \frac {B_{2 n + 2} } {B_{2 n} } } \right \rvert 2 x^2\)
\(\displaystyle \) \(=\) \(\displaystyle \lim_{n \mathop \to \infty} \left \lvert {\frac 1 {\left({2 n + 1}\right) \left({n + 1}\right)} \frac {B_{2 n + 2} } { B_{2 n} } }\right \rvert 8 x^2\)
\(\displaystyle \) \(=\) \(\displaystyle \lim_{n \mathop \to \infty} \left \lvert {\frac 1 {\left({2 n + 1}\right) \left({n + 1}\right)} \frac {\left({- 1}\right)^{n + 2} 4 \sqrt {\pi (n + 1)} \left({\frac {n + 1} {\pi e} }\right)^{2 n + 2} } {\left({- 1}\right)^{n + 1} 4 \sqrt {\pi n} \left({\frac n {\pi e} }\right)^{2 n} } } \right \rvert 8 x^2\) Asymptotic Formula for Bernoulli Numbers
\(\displaystyle \) \(=\) \(\displaystyle \lim_{n \mathop \to \infty} \left \lvert {\frac {\left({n + 1}\right)^2} {\left({2 n + 1}\right) \left({n + 1}\right)} \sqrt {\frac {n + 1} n } \left({\frac {n + 1} n }\right)^{2 n} } \right \rvert \frac 8 {\pi^2 e^2} x^2\)
\(\displaystyle \) \(=\) \(\displaystyle \lim_{n \mathop \to \infty} \left \lvert {\left({\frac {n + 1} n }\right)^{2 n} } \right \rvert \frac 4 {\pi^2 e^2} x^2\)
\(\displaystyle \) \(=\) \(\displaystyle \lim_{n \mathop \to \infty} \left \lvert {\left({\left({1 + \frac 1 n}\right)^n}\right)^2} \right \rvert \frac 4 {\pi^2 e^2} x^2\)
\(\displaystyle \) \(=\) \(\displaystyle \frac {4 e^2} {\pi^2 e^2} x^2\) Definition of Euler's Number
\(\displaystyle \) \(=\) \(\displaystyle \frac 4 {\pi^2} x^2\)

This is less than $1$ if and only if:

$\left|{x}\right| < \dfrac \pi 2$

Hence by the Ratio Test, the series converges for $\left|{x}\right| < \dfrac \pi 2$.

$\blacksquare$


Sequence of Terms

The Power Series Expansion for Tangent Function begins:

$\tan x = x + \dfrac 1 3 x^3 + \dfrac 2 {15} x^5 + \dfrac {17} {315} x^7 + \dfrac {62} {2835} x^9 + \cdots$


Sources